2010
DOI: 10.1007/s10147-010-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Ewing’s sarcoma of the kidney

Abstract: Primitive neuroectodermal tumors (PNETs) are small, round-cell tumors of neural crest origin classically found in the central nervous system (CNS) but more recently characterized in the periphery. Peripherally located PNETs (pPNETs) are members of the Ewing's sarcoma family of tumors (EFTs). Renal localization of pPNETs is very rare, is found in young adults, and is characterized by an aggressive clinical course and poor prognosis. We present the case of a young man with renal pPNET characterized by psuedorose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 19 publications
2
40
0
Order By: Relevance
“…5 Wilms tumor 1 (WT-1), a common marker for Wilms tumor, may also be used to rule against a PNET diagnosis, 3,10 although in rare instances, it may also stain positive in renal PNETs. 4 In one study, Friend leukemia virus integration 1 (FLI-1) demonstrated positive staining in 5 out of 8 cases of renal PNET and 0 out of 10 cases of Wilms tumor, indicating that this marker may aid in differentiating the two as well.…”
Section: Immunoprofilementioning
confidence: 99%
See 4 more Smart Citations
“…5 Wilms tumor 1 (WT-1), a common marker for Wilms tumor, may also be used to rule against a PNET diagnosis, 3,10 although in rare instances, it may also stain positive in renal PNETs. 4 In one study, Friend leukemia virus integration 1 (FLI-1) demonstrated positive staining in 5 out of 8 cases of renal PNET and 0 out of 10 cases of Wilms tumor, indicating that this marker may aid in differentiating the two as well.…”
Section: Immunoprofilementioning
confidence: 99%
“…4,6 Dyspnea and dizziness may also be seen if the tumor features atrial involvement. 13 Laboratory abnormalities that may be seen in renal PNET include elevated lactate dehydrogenase, glutamicoxaloacetic transaminase, glutamic-pyruvic transaminase, and creatinine.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations